2019
DOI: 10.1186/s12934-019-1209-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal proteome allocation strategies for phototrophic growth in a light-limited chemostat

Abstract: Background Cyanobacteria and other phototrophic microorganisms allow to couple the light-driven assimilation of atmospheric $$\text {CO}_{2}$$ CO 2 directly to the synthesis of carbon-based products, and are therefore attractive platforms for microbial cell factories. While most current engineering efforts are performed using small-scale laboratory cultivation, the econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The protein pool includes enzymes devoted to hundreds of reactions which may be coarse-grained into several major categories including those related to light-harvesting and electron transport, and those related to biosynthesis, growth, and reproduction ( Figure 3A). Recent proteomic analyses are quantifying broad-brush protein allocation (McKew et al, 2013(McKew et al, , 2015Christie-Oleza et al, 2017;Jahn et al, 2018;Zavřel et al, 2019) in ways which connect to such coarse-grained models (Scott et al, 2010;Burnap, 2015;Reimers et al, 2017;Faizi et al, 2018;Faizi and Steuer, 2019). Recent studies have revealed that a large and highly variable fraction of phytoplankton proteome is devoted to lightharvesting and electron transport (Jahn et al, 2018;Zavřel et al, 2019) and this investment increases as light intensity decreases.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein pool includes enzymes devoted to hundreds of reactions which may be coarse-grained into several major categories including those related to light-harvesting and electron transport, and those related to biosynthesis, growth, and reproduction ( Figure 3A). Recent proteomic analyses are quantifying broad-brush protein allocation (McKew et al, 2013(McKew et al, , 2015Christie-Oleza et al, 2017;Jahn et al, 2018;Zavřel et al, 2019) in ways which connect to such coarse-grained models (Scott et al, 2010;Burnap, 2015;Reimers et al, 2017;Faizi et al, 2018;Faizi and Steuer, 2019). Recent studies have revealed that a large and highly variable fraction of phytoplankton proteome is devoted to lightharvesting and electron transport (Jahn et al, 2018;Zavřel et al, 2019) and this investment increases as light intensity decreases.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Models of phytoplankton physiology have sought to relate growth rate (related to fitness) and elemental stoichiometry (related to biogeochemical impacts) to external resource availability (Riley, 1946;Monod, 1949), internal stores of resources (Caperon, 1968;Droop, 1968), and the internal allocation between functional pools and storage molecules (Shuter, 1979;Geider et al, 1998;Kooijman, 2010). Recent models also explicitly represent trade-offs associated with allocation of the resource and proteome (Bonachela et al, 2013;Burnap, 2015;Smith et al, 2016;Reimers et al, 2017;Chen and Smith, 2018;Faizi et al, 2018;Jahn et al, 2018;Faizi and Steuer, 2019). We provide a more comprehensive review of published physiological models in Supplementary Text.…”
Section: Introductionmentioning
confidence: 99%
“…These models are typically constrained by conservation constraints on elemental, electron and energy budgets [27] , [53] , [152] , [153] . Some coarse-grained models resolve macromolecular allocation [121] , [122] , [154] , which can be compared with emerging sources of macromolecular and proteomics data.…”
Section: Type Of Modelmentioning
confidence: 99%
“…Rapid growth and low yield occurs on abundant resources, while slow growth and high yield occurs on scarce resources. Only recently has optimal proteome allocation been analyzed in the context of phototrophy and autotrophy in general [102][103][104] , but the principles are identical when ambient light is treated as a metabolic resource.…”
Section: Retinalophototrophy Is Observed In Fully 50% Of Bacteria In mentioning
confidence: 99%